Analisis Strategi Pemasaran Objek Wisata Kebun Binatang Kasang Kulim Kecamatan Siak Hulu Kabupaten Kampar - Ona Gustina Mardianti; Syahdanur Syahdanur; Susie Suryani (Jurnal Ekonomi KIAT, 2019)
This study aims to determine the marketing strategy of the tourist attraction of the Kasang Kulim Zoo, the Siak Hulu sub-district, Kampar District. The population of this study was visitors who came to the Kasang Kulim Zoo, Siak Hulu Sub-District, Kampar District and from the company, with a number of respondents as many as 100. In this study sampling using non probability sampling and respondent sampling was done by accidental sampling technique. This research is qualitative research and uses interviews, questionnaires, and documentation as a method of data collection. Data were analyzed using SWOT analysis with identification of internal and external variables. Internal variables indicate that location is the main strength in the kasang kulim zoo in kampar district with 0.012 with values ​​and 4 based on rating. From the external variables, the results from EFAS show that the Kasang Kulim zoo has good opportunities. As a result of the opportunity, the Kasang Kulim zoo is in quadrant 1, which is a position where the company is considered to be in a favorable situation because of its opportunities and strength. In this case, the Company can take advantage of opportunities by maximizing strength.